Study and modelling of the handling of equipment: case of a self-propelled handling truck - Djami Aslain Brisco , Ngnassi; Nguelcheu Ulrich , Ngnassi; Yamigno Serge, Doka (International Journal of Engineering and Technology, 2024)
This paper is the result of an industrial problem relating to the trauma suffered by forklift truck drivers when their trucks roll over sideways. The general objective of this paper was to model the forklift truck and the operator in order to test the different accident conditions. Specifically, a parameterised model of the forklift truck and driver was statically and dynamically modelled. This model can be used to represent most cantilever and counterbalanced forklift trucks with a nominal capacity of 2,000 to 3,000 kg, whether they are powered by petrol, propane or electricity. The forklift operator was represented by a 50th percentile Hybrid III dummy. A range of safety systems (lap belt, armrests, shoulder restraints, doors) and different rollover conditions were tested: low speed (static) and high speed (dynamic). This interface is used to enter the parameters required to create models of the truck and driver, and to define the accident conditions. The results of the static and dynamic simulations show that the models of the truck and driver are functional and relatively realistic, at least according to the limited data available in the literature and according to those involved in the field. The results show that the type of floor has little influence on the driver's injuries, but that the safety systems used have a very strong influence, for both static and dynamic rollover cases. At the current stage of modelling, doors and shoulder restraints in combination with a lap belt appear to be more effective in protecting the driver than armrests with or without a lap belt or no re-straint system at all.